TEACHER STATUS IN ARTISTIC WORK - O‘tkir Yo‘ldoshev (Galaxy International Interdisciplinary Research Journal, 2021)
Teaching is a great status. He who learns and teaches in the way of truth will be glorified by the people and the Creator, and will be exalted. The spirituality and traditions of each nation are reflected in the literature of that nation. To know the status of watermelon, you need to know the literature of the people. This article discusses the reflection of the status of a teacher in Uzbek literature, the level of the status of a teacher. Thoughts about the teacher were expressed, first of all, in the works of Alisher Navoi, the flower of our classics, as well as in the first Uzbek novel "Last Days" and the national epic of our people "Alpomish" with a thousand-year history.